Molecular sieve catalyst as well as preparation method and application thereof

The molecular sieve catalyst is prepared by negative pressure-microwave induced staging crystallization method, which solves the problem of active metal migration and agglomeration in the propane dehydrogenation catalyst, and achieves the high carbon deposit resistance and stability of the catalyst, simplifies the regeneration process and improves economic benefits.

CN119588402AActive Publication Date: 2025-03-11WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202411737870.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-11
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing propane dehydrogenation catalysts are prone to migration and agglomeration of active metals during high temperature reactions, resulting in reduced catalyst activity and complex regeneration process.

Method used

The molecular sieve catalyst is prepared by negative pressure-microwave induced staging crystallization method, and a catalyst with a core-shell structure and uniform distribution of active metals are obtained through in-situ synthesis to avoid agglomeration of active metals.

Benefits of technology

The catalyst has achieved high carbon deposit resistance, stability and selectivity, simplified the regeneration process, extended the device operation cycle, and improved the economic benefits of propane dehydrogenation to propylene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005161916400000111
    Figure BDA0005161916400000111
  • Figure HDA0005161916410000011
    Figure HDA0005161916410000011
Patent Text Reader

Abstract

The invention relates to a molecular sieve catalyst as well as a preparation method and application thereof, and the preparation method of the molecular sieve catalyst comprises the following steps: (1) obtaining an all-silicon Silicate-1 molecular sieve; (2) preparing the molecular sieve catalyst: S1, uniformly mixing an all-silicon Silicate-1 molecular sieve with a silicon source, alkali, a template agent, water, a Pt source and an auxiliary agent, and aging under a negative pressure condition; s2, heating under a microwave induction condition for crystallization, and then washing, drying and roasting to obtain the molecular sieve catalyst. The prepared catalyst shows excellent stability and carbon deposition resistance and higher propylene product selectivity in a reaction for preparing propylene through propane dehydrogenation, and the catalyst is beneficial for prolonging the operation cycle of a device and reducing the unit consumption of the reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic dehydrogenation of propane to produce propylene, relates to a novel catalyst and a preparation method and application thereof, and specifically relates to a method for preparing the catalyst by negative pressure-microwave induced graded crystallization. Background Art

[0002] With the rapid development of social economy, the market demand for propylene has increased year by year. Propane dehydrogenation has attracted much attention due to its unique technical advantages and high propylene selectivity. At present, there are only two propane dehydrogenation processes that have been applied on a large scale in the world, namely the Catofin process developed by ABB Lummus in the United States and the Oleflex process developed by UOP. Among them, the catalyst used in the Catofin process is a chromium-based catalyst, which is toxic to the environment. The catalyst used in the Oleflex process is a platinum-based catalyst prepared by the traditional impregnation method. Due to its preparation characteristics, the active precious metal will gradually agglomerate during the reaction and lose its high selectivity and activity for propylene. Therefore, the catalyst needs to be regenerated by oxychlorination after a period of use, and the introduction of chlorine will increase the risk of the process and the complexity of the regeneration operation.

[0003] Molecular sieve-based catalysts have shown great advantages in the field of catalysis due to their unique molecular skeleton structure, pore size and interaction with related active metals. Through reasonable synthesis methods and regulation of synthetic components, it is expected to achieve the preparation of high-performance catalyst products.

[0004] Chinese patent CN1602997A discloses a method for microwave-assisted synthesis of perovskite catalysts, which exhibits good electrocatalytic activity. However, the catalyst is not suitable for the field of propane dehydrogenation. Chinese patent CN104556131A discloses a method for preparing a propane dehydrogenation catalyst with controllable Pt grains. The patent uses Sn-containing alumina as a carrier and prepares a highly dispersed, particle-size-controlled, high-catalytic activity propane dehydrogenation catalyst by heating and refluxing under a vacuum environment. However, the method provided by the patent is an optimization innovation on the traditional loading method, but the prepared catalyst is essentially a loaded catalyst, and it is difficult to overcome the agglomeration of active metals during the reaction.

[0005] Therefore, it is necessary to develop a new type of catalyst that can overcome the problems of migration and agglomeration of active metals during the high temperature reaction when used in the field of propane catalytic dehydrogenation to propylene. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a new type of molecular sieve catalyst and preparation method, which has high resistance to carbon deposition, stability and selectivity, can simplify the regeneration process of traditional propane dehydrogenation catalyst, and effectively improve and extend the operation cycle of the device, thereby improving the economic benefits of the propane dehydrogenation to propylene production process.

[0007] To achieve the above purpose, the present invention adopts an in-situ synthesis catalyst preparation method, and obtains a molecular sieve catalyst with a core-shell structure and uniformly dispersed active metals on the outer surface by rationally utilizing negative pressure, microwaves and other means. Due to the strong interaction between the molecular sieve skeleton structure and the active components and the confined characteristics of the pore structure, the migration and agglomeration of active metals during the high temperature reaction process can be effectively overcome, thereby simplifying the regeneration process of the traditional propane dehydrogenation catalyst (no chlorine injection is required during the regeneration process), and showing excellent stability, anti-carbon deposition performance and higher propylene product selectivity. The catalyst is beneficial to extending the operating cycle of the device and reducing the reaction unit consumption.

[0008] In one aspect, the present invention provides a method for preparing a molecular sieve catalyst, comprising the following steps:

[0009] (1) Obtaining all-silica Silicate-1 molecular sieve;

[0010] (2) Preparation of molecular sieve catalyst:

[0011] S1: Mix the Silicate-1 molecular sieve with the silicon source, alkali, template, water, Pt source and additives evenly, and age them under negative pressure;

[0012] S2: heating under microwave induction conditions for crystallization, followed by washing, drying and calcining to obtain the molecular sieve catalyst.

[0013] Step (1) of the present invention is a method for obtaining an all-silicon Silicate-1 molecular sieve. The all-silicon Silicate-1 molecular sieve of the present invention is a product disclosed in the prior art and can be purchased through common commercial channels or prepared by referring to existing conventional processes. The present method has no specific requirements for its acquisition source. For example, in one embodiment, the all-silicon Silicate-1 molecular sieve can be prepared according to the following method, comprising the steps of:

[0014] The silicon source, alkali, template agent and water are mixed, and then crystallized, washed, dried and calcined to obtain the all-silicon Silicate-1 molecular sieve;

[0015] Wherein, the mixing mass ratio of the silicon source, the alkali, the template and the water is 1.0: (0.05-5): (0.2-0.5): (2-5); specifically, in this mass ratio, based on the silicon source value of 1.0, the alkali can be 0.05, 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two thereof, the template can be 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or a range consisting of any two thereof, and the water can be 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two thereof;

[0016] Wherein, the silicon source is selected from one or more of organic silicon and inorganic silicon sources, preferably one or more of sodium silicate, white carbon black, ethyl orthosilicate, and silica sol;

[0017] Wherein, the base is selected from one or more of ammonia water and metal hydroxides, preferably one or more of ammonia water, barium hydroxide, sodium hydroxide, potassium hydroxide and calcium hydroxide;

[0018] Wherein, the template agent is selected from one or more of ammonia compounds, preferably one or more of butylamine, ethylamine, tetrabutylammonium bromide, tetraethylammonium bromide, tetrapropylammonium hydroxide, and tetrapropylammonium bromide;

[0019] Wherein, the mixing, crystallization, washing, drying and calcining are conventional operations in the field, and the specific parameters can be screened according to actual conditions; preferably, the mixing process controls the stirring speed to be 50-700r / min, and the stirring time is 30-240min; preferably, the crystallization process controls the temperature to be 160-190°C, and the time is 16-72h; specifically, the stirring speed includes but is not limited to 50r / min, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 600r / min, 700r / min or any two thereof. The stirring time includes but is not limited to 30 min, 50 min, 80 min, 100 min, 130 min, 150 min, 180 min, 200 min, 220 min, 240 min or a range consisting of any two thereof; the crystallization process temperature can be 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C or a range consisting of any two thereof, and the time can be 16h, 20h, 30h, 40h, 50h, 60h, 70h, 72h or a range consisting of any two thereof.

[0020] In step (2) of the present invention, a molecular sieve catalyst is prepared based on the obtained all-silicon Silicate-1 molecular sieve. The all-silicon Silicate-1 molecular sieve obtained by the crystallization method is fully mixed and stirred with the other raw materials in a certain proportion, and then vacuumed and negative pressure aged for a period of time. The aged sample is subjected to microwave heating to induce secondary crystallization to obtain the catalyst.

[0021] In one embodiment, the silicon source in step S1 is selected from one or more of organic silicon and inorganic silicon sources, preferably one or more of sodium silicate, white carbon black, tetraethyl orthosilicate, and silica sol.

[0022] In one embodiment, the base in step S1 is selected from one or more of ammonia water and metal hydroxides, preferably one or more of ammonia water, barium hydroxide, sodium hydroxide, potassium hydroxide and calcium hydroxide;

[0023] In one embodiment, the template in step S1 includes one or more selected from ammonia compounds, preferably one or more selected from tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetrapropylammonium hydroxide, ethylamine, and butylamine.

[0024] In one embodiment, the Pt source in step S1 is selected from one or more of H2PtCl6·6H2O, [Pt(NH3)2(NO2)2].

[0025] In one embodiment, the auxiliary agent in step S1 is selected from C 10 H 12 MgN2Na2O8·4H2O、C 10 H 12 ZnN2Na2O8·4H2O、C 10 H 12 One or more of FeN2Na2O8, MgSO4, MgCl2, KCl, K2SO4, La(NO3)3, InCl3, LaCl3, YCl3, CeCl3.

[0026] In one embodiment, the mass ratio of the all-silicon Silicate-1 molecular sieve to the silicon source, alkali, template, and water in step S1 is 1.0: (0.1-0.5): (0.03-0.16): (0.08-0.4): (1.2-5.5); specifically, in this mass ratio, based on the all-silicon Silicate-1 molecular sieve taking a value of 1.0, the silicon source can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or any two thereof. the alkali may be 0.03, 0.05, 0.07, 0.09, 0.11, 0.13, 0.15, 0.16 or a range consisting of any two thereof, the template may be 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4 or a range consisting of any two thereof, and the water may be 1.2, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5 or a range consisting of any two thereof.

[0027] In one embodiment, the amount of Pt source in step S1 is 0.05-0.5wt% of the mass of the all-silicon Silicate-1 molecular sieve, including but not limited to 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt% or a range consisting of any two thereof.

[0028] In one embodiment, the amount of the auxiliary agent in step S1 is 0.02-0.5wt% of the mass of the all-silicon Silicate-1 molecular sieve, including but not limited to 0.02wt%, 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt% or a range consisting of any two thereof.

[0029] In one embodiment, the uniform mixing in step S1 is achieved by sufficient stirring, and the mixing process controls the stirring speed to be 50-600r / min, and the stirring time to be 30-240min; specifically, the stirring speed includes but is not limited to 50r / min, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 600r / min or a range consisting of any two thereof, and the stirring time includes but is not limited to 30min, 50min, 80min, 100min, 130min, 150min, 180min, 200min, 220min, 240min or a range consisting of any two thereof.

[0030] In one embodiment, aging is carried out under negative pressure conditions in step S1, by transferring the material to a reaction tube and evacuating the tube for treatment. There is no special requirement for the temperature of the aging process. For example, it can be carried out at room temperature, the pressure is -(0.5-0.01) MPa, and the time is 0.5-62h. Specifically, the pressure can be -0.5MPa, -0.45MPa, -0.4MPa, -0.35MPa, -0.3MPa, -0.25MPa, -0.2MPa, -0.15MPa, -0.1MPa, -0.05MPa, -0.01MPa or a range consisting of any two thereof, and the time can be 0.5h, 1h, 10h, 20h, 30h, 40h, 50h, 60h, 62h or a range consisting of any two thereof.

[0031] In one embodiment, step S2 is performed by heating under microwave induction conditions for crystallization, and the crystallization is completed by transferring the material after negative pressure aging into a microwave heating furnace for microwave induced heating. The crystallization is heated at a temperature of 90°C-195°C for a time of 0.5-32h. Specifically, the temperature may be 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 195°C or a range consisting of any two thereof, and the time may be 0.5h, 1h, 5h, 10h, 15h, 20h, 25°C, 30h, 32h or a range consisting of any two thereof.

[0032] In one embodiment, the microwave induction in step S2 has a microwave power of 0.2-10 kW, including but not limited to 0.2 kW, 0.5 kW, 1 kW, 2 kW, 3 kW, 4 kW, 5 kW, 7 kW, 9 kW, 10 kW or a range between any two thereof.

[0033] After the microwave-induced heating crystallization in step S2 of the present invention, washing, drying and calcining operations are also included, wherein the washing, drying and calcining are conventional operations in the field, and the specific parameters can be screened according to actual conditions, and the present invention has no special requirements; preferably, the washing is performed with deionized water until neutral; preferably, the drying temperature is 60-120°C and the time is 12-24h; preferably, the calcining temperature is 450-590°C and the time is 3-8h; specifically, the drying temperature can be 60°C, 70°C, 80°C, The calcination temperature may be 450°C, 470°C, 490°C, 500°C, 520°C, 550°C, 570°C, 590°C or a range consisting of any two thereof, and the calcination time may be 3h, 4h, 5h, 6h, 7h, 8h or a range consisting of any two thereof.

[0034] On the other hand, the present invention provides a molecular sieve catalyst prepared by the above method, the catalyst having a core-shell structure and the active metal on the outer surface is evenly dispersed;

[0035] Specifically, the catalyst has active precious metals mainly distributed in the shallow surface area above 20 nm. The characterization results show that when the depth exceeds 30 nm, the presence of Pt metal can basically no longer be detected, indicating that the active precious metal Pt of the catalyst prepared by the present invention is mainly distributed on the outer surface of the catalyst sample. In addition, the Pt dispersion characterization results show that the active metal dispersion of the catalyst can reach more than 90%.

[0036] In another aspect, the present invention also provides use of the molecular sieve catalyst described above as a dehydrogenation catalyst.

[0037] The catalyst of the present invention can be used in the fields of carbon three dehydrogenation, carbon four dehydrogenation, methanol to olefins, etc., and is particularly suitable for catalytic dehydrogenation of propane to produce propylene.

[0038] In one embodiment, the method for preparing propylene by catalytic dehydrogenation of propane as described above can use a conventional reactor in the art to carry out the dehydrogenation reaction. For example, the reactor used can be a fluidized bed reactor or a fixed bed tank reactor.

[0039] Specifically, a method for preparing propylene by catalytic dehydrogenation of propane is to pass propane / hydrogen into a fixed bed filled with the molecular sieve catalyst of the present invention for reaction. The relevant operations and process conditions in the preparation method of the present invention, and the devices used therein, can be carried out by using the corresponding conventional selections in the art, and there is no particular limitation thereto. The technicians can optimize the known processes in the prior art according to actual needs, and specifically, for example, the conditions listed in the following embodiments of the present invention can be used:

[0040] The molar ratio of hydrogen to hydrocarbon (propane / hydrogen) in the raw gas is 0.1-0.5, including but not limited to 0.1, 0.2, 0.3, 0.4, 0.5 or a range consisting of any two thereof;

[0041] The reaction space velocity is 400-1500 hr -1 , calculated based on the catalyst volume and total reaction feed, including but not limited to 400hr -1 、600hr -1 、800hr -1 、1000hr -1 、1200hr -1 、1400hr -1 、1500hr -1 or a range between any two of them;

[0042] The reaction has a pressure of 0.101-0.15 MPa and a temperature of 560-620°C. Specifically, the pressure may be 0.101 MPa, 0.11 MPa, 0.12 MPa, 0.13 MPa, 0.14 MPa, 0.15 MPa or a range consisting of any two thereof, and the temperature may be 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C or a range consisting of any two thereof.

[0043] The molecular sieve catalyst of the present invention can maintain its performance through regeneration operation during the production process. Specifically, the catalyst regeneration method is to introduce a gas at a temperature of 480-620°C and a space velocity of 1200-4500h -1 The air is regenerated for 0.5-3.5 hours; specifically, the temperature can be 480°C, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C or a range between any two thereof, and the air velocity can be 1200 hr -1 、1500hr -1 、2000hr -1 、2500hr -1 、3000hr -1 、3500hr-1 、4000hr -1 、4500hr -1 Or a range consisting of any two thereof, the time may be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h or a range consisting of any two thereof.

[0044] In practical applications, the regeneration process is performed online after the reaction is completed, and the end of the regeneration process is a cycle. After multiple rounds of cyclic regeneration, the catalyst of the present invention still maintains a high reaction performance, and the amount of catalyst carbon deposition remains basically stable.

[0045] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0046] The present invention provides a novel molecular sieve catalyst and a preparation method thereof, which can effectively overcome the migration and agglomeration of active metals during the high temperature reaction process, can simplify the regeneration process of the conventional propane dehydrogenation catalyst, does not require chlorine injection during the regeneration process, reduces the carbon deposit content, prolongs the service life of the catalyst and the operation cycle of the device, and realizes low-cost continuous operation of the catalytic propane dehydrogenation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 The curves of conversion rate and selectivity of propane dehydrogenation reaction changing with time for the three catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 under the same experimental conditions are shown. DETAILED DESCRIPTION

[0048] The present invention is exemplarily described below in conjunction with specific implementation modes, but it should be understood that the protection of the present invention is not limited to the specific implementation modes.

[0049] In the embodiments and comparative examples of the present invention, the raw materials and reagents used were purchased from commercial sources unless otherwise specified.

[0050] Preparation of all-silicon Silicate-1 molecular sieve: First, weigh 263.4g of deionized water and 64g of ethyl orthosilicate, pour them into a beaker and stir evenly, and control the speed to 250-700r / min. Weigh 3.72g of NaOH and 13.64g of TPAOH (tetrapropylammonium bromide) into a beaker and stir for 30min at room temperature. Then transfer the mixture to a stainless steel kettle and place it in an oven for crystallization, where the crystallization temperature is 170°C and the crystallization time is 36h. After the crystallization is completed, the sample is washed, dried, and calcined.

[0051] [Example 1]

[0052] The steps for preparing the molecular sieve catalyst are:

[0053] S1: Weigh 100g Silicate-1 molecular sieve, 238.2g deionized water and 17.5g ethyl orthosilicate, pour into a 500mL beaker and stir evenly, and control the speed to 150-600r / min. Weigh 0.4g H2PtCl6·6H2O, 0.32g MgCl2 and 0.15g InCl3, add to the beaker, mix and stir evenly, weigh 3.98g NaOH and 9.67g tetrapropylammonium bromide, add to the beaker and continue stirring for 90min. Then transfer the mixture to the reaction tube and evacuate it to -0.2MPa, and maintain the negative pressure state for aging for 48h.

[0054] S2: The sample after negative pressure aging was transferred to a microwave heating furnace, the microwave induced power was set to 1.5kW, the microwave heating temperature was controlled to 175°C, and the temperature was maintained for 16 hours to complete the secondary crystallization. After the sample was cooled to room temperature, the slurry was taken out and washed with deionized water and filtered until the pH was neutral. The filtered sample was placed in an oven at 60-120°C for 12 hours, and then calcined in a muffle furnace at 550°C for 6 hours to obtain a molecular sieve catalyst.

[0055] The catalyst has a distinct core-shell structure, and the active metals are evenly distributed on the outer surface. The active precious metals are mainly distributed in the shallow surface area of ​​20-30nm. The characterization results show that when the depth exceeds 30nm, the presence of Pt metal can basically no longer be detected, indicating that the active precious metal Pt of the catalyst prepared by the present invention is mainly distributed on the outer surface of the catalyst sample. In addition, the Pt dispersion characterization results show that the active metal dispersion of the catalyst reaches 93.2%.

[0056] [Example 2]

[0057] The steps for preparing the molecular sieve catalyst are:

[0058] S1: Weigh 90g Silicate-1 molecular sieve, 396.5g deionized water and 35g silica sol, pour into a 500mL beaker and stir evenly, control the speed to 150-600r / min. Weigh 0.28g [Pt(NH3)2(NO2)2], 0.12g C 10 H 12 Add ZnN2Na2O8·4H2O to the beaker and mix well. Weigh 5g potassium hydroxide and 12g tetrabutylammonium bromide and add them to the beaker and continue stirring for 90 minutes. Then transfer the mixture to the reaction tube and evacuate it to -0.15MPa. Maintain the negative pressure and let it stand for aging for 36 hours.

[0059] S2: The sample after negative pressure aging was transferred to a microwave heating furnace, the microwave induced power was set to 2.2kW, the microwave heating temperature was controlled to 160°C, and the temperature was maintained for 24 hours to complete the secondary crystallization. After the sample was cooled to room temperature, the slurry was taken out and washed with deionized water and filtered until the pH was neutral. The filtered sample was placed in an oven at 60-120°C for 12 hours, and then calcined in a muffle furnace at 550°C for 6 hours to obtain a molecular sieve catalyst.

[0060] The catalyst has a distinct core-shell structure, and the active metals are evenly distributed on the outer surface. The active precious metals are mainly distributed in the shallow surface area of ​​20-30nm. The characterization results show that when the depth exceeds 30nm, the presence of Pt metal can basically no longer be detected, indicating that the active precious metal Pt of the catalyst prepared by the present invention is mainly distributed on the outer surface of the catalyst sample. In addition, the Pt dispersion characterization results show that the active metal dispersion of the catalyst reaches 92.1%.

[0061] [Example 3]

[0062] The steps for preparing the molecular sieve catalyst are:

[0063] S1: Weigh 110g Silicate-1 molecular sieve, 245g deionized water and 20g sodium silicate, pour into a 500mL beaker and stir evenly, and control the speed to 150-600r / min. Weigh 0.39g H2PtCl6·6H2O and 0.35g La(NO3)3, add them to the beaker, mix and stir evenly, weigh 15g ammonia water and 25g tetrapropylammonium hydroxide, add them to the beaker and continue stirring for 90min. Then transfer the mixture to the reaction tube and evacuate it to -0.05MPa, and maintain the negative pressure state for aging for 48h.

[0064] S2: The sample after negative pressure aging was transferred to a microwave heating furnace, the microwave induced power was set to 5kW, the microwave heating temperature was controlled to 195°C, and the temperature was maintained for 12 hours to complete the secondary crystallization. After the sample was cooled to room temperature, the slurry was taken out and washed with deionized water and filtered until the pH was neutral. The filtered sample was placed in an oven at 60-120°C for 12 hours, and then calcined in a muffle furnace at 550°C for 6 hours to obtain a molecular sieve catalyst.

[0065] The catalyst has a distinct core-shell structure, and the active metals are evenly distributed on the outer surface. The active precious metals are mainly distributed in the shallow surface area of ​​30-40nm. The characterization results show that when the depth exceeds 40nm, the presence of Pt metal can basically no longer be detected, indicating that the active precious metal Pt of the catalyst prepared by the present invention is mainly distributed on the outer surface of the catalyst sample. In addition, the Pt dispersion characterization results show that the active metal dispersion of the catalyst reaches 90.7%.

[0066] [Example 4]

[0067] The steps for preparing the molecular sieve catalyst are:

[0068] S1: Weigh 100g Silicate-1 molecular sieve, 329g deionized water and 21g white carbon black, pour into a 500mL beaker and stir evenly, control the speed to 150-600r / min. Weigh 0.12g H2PtCl6·6H2O, 0.2gC 10 H 12 MgN2Na2O8·4H2O and 0.1g La(NO3)3 were added to a beaker and mixed and stirred evenly. 7.5g barium hydroxide and 19g tetrapropylammonium bromide were weighed and added to the beaker and stirred for 90 minutes. The mixture was then transferred to a reaction tube and vacuumed to -0.2MPa. The negative pressure was maintained and allowed to stand for aging for 62 hours.

[0069] S2: The sample after negative pressure aging was transferred to a microwave heating furnace, the microwave induced power was set to 1.0kW, the microwave heating temperature was controlled to 170°C, and the temperature was maintained for 18 hours to complete the secondary crystallization. After the sample was cooled to room temperature, the slurry was taken out and washed with deionized water and filtered until the pH was neutral. The filtered sample was placed in an oven at 60-120°C for 12 hours, and then calcined in a muffle furnace at 550°C for 6 hours to obtain a molecular sieve catalyst.

[0070] The catalyst has a distinct core-shell structure, and the active metals are evenly distributed on the outer surface. The active precious metals are mainly distributed in the shallow surface area of ​​20-30nm. The characterization results show that when the depth exceeds 30nm, the presence of Pt metal can basically no longer be detected, indicating that the active precious metal Pt of the catalyst prepared by the present invention is mainly distributed on the outer surface of the catalyst sample. In addition, the Pt dispersion characterization results show that the active metal dispersion of the catalyst is more than 92.6%.

[0071] [Comparative Example 1]

[0072] This comparative example uses basically the same raw materials and processes as Example 1 to prepare the catalyst, with the only difference being that the pressure during the aging process is 0 MPa (normal pressure), and the secondary crystallization process does not use microwave induction but conventional oven heating, and other operations and conditions remain unchanged to obtain the catalyst.

[0073] The active metal of the catalyst is irregularly dispersed inside the catalyst, and the surface active metal distribution is poor. In addition, the Pt dispersion characterization results show that the active metal dispersion of the catalyst is 76.4%.

[0074] [Comparative Example 2]

[0075] In this comparative example, the catalyst was prepared using raw materials and processes that are substantially the same as those in Example 1, with the only difference being that the pressure during the aging process was 0 MPa (normal pressure), and other operations and conditions remained unchanged to obtain the catalyst.

[0076] The distribution of active metals on the catalyst surface is normal. In addition, the Pt dispersion characterization results show that the active metal dispersion of the catalyst is 80.5%.

[0077] [Comparative Example 3]

[0078] In this comparative example, the catalyst was prepared by using the same raw materials and process as in Example 1, except that conventional oven heating was used instead of microwave induction for secondary crystallization, and other operations and conditions remained unchanged to obtain the catalyst.

[0079] The catalyst has a preliminary core-shell structure, and the surface active metal is distributed relatively evenly. In addition, the Pt dispersion characterization results show that the active metal dispersion of the catalyst is 86.9%.

[0080] [Example 5]

[0081] Analysis and comparison of the metal dispersion properties of the catalysts prepared in each embodiment and comparative example

[0082] The CO-pulse adsorption experimental method was used to characterize the precious metal platinum dispersion of the catalyst samples of Examples 1-4 and Comparative Examples 1-3, respectively, using a chemical adsorption instrument model of Micromeritics AutoChemⅡ2920. The characterization results are shown in Table 2.

[0083] Table 1 Test results of Pt dispersion of catalyst samples of Examples 1-4 and Comparative Examples 1-3

[0084] catalyst Aging process stress Microwave induced power <![CDATA[Pt Dispersion ① > Example 1 -0.20MPa 1.5kW 93.2% Example 2 -0.15MPa 2.2kW 92.1% Example 3 -0.05MPa 5.0kW 90.7% Example 4 -0.20MPa 1.0kW 92.6% Comparative Example 1 0MPa(normal pressure) - 76.4% Comparative Example 2 0MPa(normal pressure) 1.5kW 80.5% Comparative Example 3 -0.20MPa - 86.9%

[0085] Note ①: Pt dispersion is calculated by the amount of CO adsorbed by the sample detected by TCD

[0086] It can be seen from the data in Table 1 that the molecular sieve catalyst prepared by the method of the present invention exhibits good active metal dispersion, and the Pt dispersion is tested to be above 90%, while the Pt dispersion of the catalyst sample prepared by the conventional hydrothermal synthesis method in Comparative Example 1 is only 76.4%. According to previous related studies, a higher Pt active metal dispersion helps to reduce side reactions such as thermal cracking during the propane dehydrogenation reaction. Therefore, in the catalytic performance evaluation process (see Figure 1), the catalyst sample of the present invention exhibits higher propylene selectivity. In addition, a comprehensive comparison of the analysis results of the examples and comparative samples shows that, compared with the microwave induced power in the secondary crystallization process, the vacuum negative pressure treatment process in the aging process plays a decisive role in the difference in Pt dispersion of the samples, and has a relatively lower aging process pressure, which is beneficial to promoting the dispersion of Pt in the catalyst sample.

[0087] Analysis and comparison of the distribution of active metals at different depths in the catalysts prepared in Example 1 and Comparative Example 1

[0088] The XPS-sputtering characterization method was adopted (the selected instrument model was the Thermo Fisher K-Alpha photoelectron spectrometer produced in the United States). The sputtering depth of this experiment was 0 to 50 nm. The experimental results are shown in Table 2.

[0089] Table 2 Test results of active metal distribution in catalyst

[0090]

[0091] From the content distribution data of Pt metal in the catalyst at different sputtering depths in Table 2, it can be seen that the active precious metal in Example 1 is mainly distributed in the shallow surface area above 20 nm. When the sputtering depth exceeds 30 nm, the presence of Pt metal can basically no longer be detected, indicating that the active precious metal Pt in the catalyst prepared by the present invention is mainly distributed on the outer surface of the catalyst sample, which is conducive to rapid adsorption reaction and diffusion desorption, avoids deep reaction, and finally shows higher selectivity for propylene in the propane dehydrogenation reaction (see Figure 1 ). However, in contrast, in Comparative Example 1, a relatively large Pt distribution of 0.374-0.481 wt% was detected in the sputtering depth range of 0-50 nm, and no obvious gradient difference was shown, so that it was difficult to control side reactions such as deep cracking during the reaction process, affecting the dehydrogenation reaction performance of the catalyst.

[0092] [Example 6]

[0093] The catalytic activity, propylene selectivity, reaction stability and anti-carbon deposition performance of the catalysts prepared in Examples 1-4 and Comparative Examples 1-3 in the propane dehydrogenation reaction were evaluated using a conventional fixed bed bench test apparatus. The specific experimental conditions are as follows:

[0094] The inert ceramic balls and the catalyst to be tested were loaded in layers from top to bottom in the reaction tube, with the loading volumes being 8 mL and 4 mL respectively, and the reaction space velocity was set at 1200 hr -1 The molar ratio of raw gas hydrogen to hydrocarbon (propane / hydrogen) is 0.5, the reaction pressure is set to 0.05MPa, and the reaction temperature is 605°C.

[0095] Under the same experimental conditions as above, the test results of the carbon deposit content of the catalyst (measured by a carbon sulfur analyzer) after each catalyst reacted continuously for 50 hours are shown in Table 3. In addition, the catalytic performance curves of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 over time are shown in Table 3. Figure 1 shown.

[0096] Table 3 Long-term reaction test results of catalysts

[0097] sample Catalyst carbon deposit content Propylene selectivity / % Example 1 1.87wt% 95.6 Example 2 2.05wt% 94.5 Example 3 2.39wt% 93.1 Example 4 2.16wt% 93.8 Comparative Example 1 9.47wt% 79.5 Comparative Example 2 6.32wt% 84.9 Comparative Example 3 5.85wt% 88.9

[0098] In order to further verify the stability of the catalyst of the present invention in multiple rounds of regeneration cycles and a simpler regeneration operation process, the molecular sieve catalyst of Example 1 was selected here to carry out multiple rounds of regeneration performance tests, each round of reaction time was 50 hours, and then the regeneration process was carried out, and the end of the regeneration process was a cycle. The regeneration process was carried out at 520°C and the air velocity was 2400h. -1 The regeneration was carried out with air for 2h. The results are shown in Table 4.

[0099] Table 4 Multi-cycle regeneration performance test results

[0100] Propylene yield Carbon deposit amount A regeneration cycle 42.5% 1.92wt% Two-round regeneration cycle 42.4% 1.95wt% Three-wheel regeneration cycle 42.2% 1.98wt% Four-wheel regeneration cycle 42.1% 2.01wt% Five regeneration cycles 42.1% 2.02wt%

[0101] It can be seen from the data in Table 3 that under exactly the same experimental conditions, the molecular sieve catalyst prepared in the present invention has stronger resistance to carbon deposition. After 50 hours of continuous propane dehydrogenation reaction, the carbon deposition content of the catalyst is maintained below 2.5 wt%, showing good reaction stability. However, when only one of negative pressure, microwave induced crystallization or traditional hydrothermal synthesis is used, the carbon deposition content of the catalyst increases significantly after the reaction. Among them, the sample prepared by traditional hydrothermal synthesis method in Comparative Example 1 has a carbon deposition content as high as 9.47 wt%.

[0102] It can be seen from the results in Table 4 that the present invention does not adopt the industrial Pt-based catalyst oxychlorination reduction regeneration method that requires the injection of chlorine. Example 1 still maintains a high reaction performance under multiple rounds of air regeneration conditions, the catalyst carbon deposition amount remains basically stable, and the propylene yield is maintained at more than 40%, showing excellent regeneration stability.

[0103] In addition, by Figure 1The reaction performance curve of the catalyst over time also shows that the catalyst prepared according to the present invention has higher propylene selectivity and reaction stability. After 50 hours of continuous reaction, the catalyst activity remains basically unchanged (the propane conversion rate decreases by less than 1%), and the propylene selectivity is higher than that of the comparative example sample. However, after a long period of continuous reaction, the catalyst activity of the comparative example 1 sample has been significantly reduced, indicating that most of the active components on the catalyst have been covered by carbon deposits and cannot play a catalytic effect, and there are few active components available for the reaction. It can be seen from the reaction test results that under the same experimental conditions, the catalyst prepared by the method of the present invention can achieve a higher propylene selectivity of 95.6%, which is 4.1 percentage points higher than the traditional hydrothermal synthesis method, and the propane unit consumption can be reduced by 47kg, equivalent to 235 yuan / t propylene.

[0104] Therefore, through the negative pressure-microwave induced fractional crystallization method of the present invention, a molecular sieve catalyst with good anti-carbon deposition performance and higher propylene selectivity can be obtained, which is of great significance for extending the reaction cycle and reducing the propane unit consumption in the process of propane dehydrogenation to produce propylene.

Claims

1. A method for preparing a molecular sieve catalyst, characterized in that: The steps include: (1) Obtaining all-silica Silicate-1 molecular sieve; (2) Preparation of molecular sieve catalyst: S1: Mix the Silicate-1 molecular sieve with the silicon source, alkali, template, water, Pt source and additives evenly, and age them under negative pressure; S2: heating under microwave induction conditions for crystallization, followed by washing, drying and calcining to obtain the molecular sieve catalyst.

2. The preparation method according to claim 1, characterized in that: The all-silicon Silicate-1 molecular sieve in step (1) is prepared according to the following method, which comprises: The silicon source, alkali, template agent and water are mixed, and then crystallized, washed, dried and calcined to obtain the all-silicon Silicate-1 molecular sieve; Preferably, the mixing mass ratio of the silicon source, alkali, template agent and water is 1.0:(0.05-5):(0.2-0.5):(2-5); Preferably, the silicon source is selected from one or more of organic silicon and inorganic silicon sources, preferably one or more of sodium silicate, white carbon black, ethyl orthosilicate, and silica sol; Preferably, the base is selected from one or more of ammonia water and metal hydroxides, preferably one or more of ammonia water, barium hydroxide, sodium hydroxide, potassium hydroxide and calcium hydroxide; Preferably, the template agent is selected from one or more of ammonia compounds, preferably one or more of butylamine, ethylamine, tetrabutylammonium bromide, tetraethylammonium bromide, tetrapropylammonium hydroxide, and tetrapropylammonium bromide; Preferably, in the mixing process, the stirring speed is 50-350 r / min and the stirring time is 30-240 min; Preferably, the crystallization process is controlled at a temperature of 160-190° C. and a time of 16-72 hours.

3. The preparation method according to claim 1, characterized in that: The silicon source in step S1 is selected from one or more of organic silicon and inorganic silicon, preferably one or more of sodium silicate, white carbon black, tetraethyl orthosilicate, and silica sol; and / or The base in step S1 is selected from one or more of ammonia water and metal hydroxides, preferably one or more of ammonia water, barium hydroxide, sodium hydroxide, potassium hydroxide and calcium hydroxide; and / or Step S1: the template agent comprises one or more selected from ammonia compounds, preferably one or more selected from tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetrapropylammonium hydroxide, ethylamine, and butylamine; and / or The Pt source in step S1 is selected from one or more of H2PtCl6·6H2O, [Pt(NH3)2(NO2)2]; and / or The auxiliary agent in step S1 is selected from C 10 H 12 MgN2Na2O8·4H2O、C 10 H 12 ZnN2Na2O8·4H2O、C 10 H 12 One or more of FeN2Na2O8, MgSO4, MgCl2, KCl, K2SO4, La(NO3)3, InCl3, LaCl3, YCl3, CeCl3.

4. The preparation method according to claim 1 or 3, characterized in that: The mass ratio of the Silicate-1 molecular sieve to the silicon source, the base, the template and the water in step S1 is 1.0:(0.1-0.5):(0.03-0.16):(0.08-0.4):(1.2-5.5); and / or The amount of Pt source in step S1 is 0.05-0.5wt% of the mass of Silicate-1 molecular sieve; and / or The dosage of the auxiliary agent in step S1 is 0.02-0.5wt% of the mass of the Silicate-1 molecular sieve.

5. The preparation method according to claim 1, characterized in that: In step S1, the mixing is performed at a stirring speed of 50-350 r / min and a stirring time of 30-240 min; and / or In the aging process of step S1, the pressure is -(0.5-0.01)MPa and the time is 0.5-62h.

6. The preparation method according to claim 1, characterized in that: In step S2, the crystallization is carried out at a heating temperature of 90°C to 195°C for a time of 0.5 to 32 hours; and / or The microwave induction in step S2 has a microwave power of 0.2-10 kilowatts; and / or The drying temperature in step S2 is 60-120°C and the drying time is 12-24h; and / or The calcination temperature in step S2 is 450-590° C. and the calcination time is 3-8 hours.

7. A molecular sieve catalyst prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the molecular sieve catalyst prepared by the preparation method according to any one of claims 1 to 6 as a dehydrogenation catalyst; Preferably, the catalyst can be used in the fields of carbon three dehydrogenation, carbon four dehydrogenation, and methanol to olefins, and is particularly suitable for catalytic dehydrogenation of propane to produce propylene.

9. A method for preparing propylene by catalytic dehydrogenation of propane, characterized in that: The method is to pass propane / hydrogen into a fixed bed filled with the molecular sieve catalyst according to claim 7 to carry out a reaction to obtain: Preferably, the propane / hydrogen molar ratio is 0.1-0.5; Preferably, the reaction space velocity is 400-1500 hr -1 , calculated based on the catalyst volume and total reaction feed; Preferably, the reaction is carried out at a pressure of 0.101-0.15 MPa and a temperature of 560-620°C.

10. The method according to claim 9, characterized in that The molecular sieve catalyst maintains its performance through regeneration operation, and the regeneration method is to pass a gas at a space velocity of 1200-4500h at 480-620°C. -1 The air is regenerated for 0.5-3.5h.

Citation Information

Patent Citations

  • Microwave synthesis method of ZSM-5 / Silicalite-1 core-shell molecular sieve

    CN104556131A

  • Microwave synthesizing calcium-titanium structure catalyst and electrocatalytic material and its manufacturing method

    CN1602997A

  • Air purification material

    CN109603895A

  • Catalyst with propane dehydrogenation catalysis function, preparation method and application of catalyst, and propane dehydrogenation method

    CN113856737A

  • Microwave-assisted composite nanomaterial catalyst, and preparation method and application thereof

    CN116747899A

Cited By

  • Method for improving diffusion rate by directionally passivating and modifying surface silicon hydroxyl of MFI type molecular sieve

    CN120618519A